The Impact of Collaborative Learning on Interpersonal Intelligence - Andi Mursidi; Buyung Buyung; Eka Murdani; Pratiwi Pratiwi; Sulha Sulha; Rustam Rustam (Universitas Negeri Makassar, 2023)
This research aims at examining the impact of collaborative learning on children’s interpersonal intelligence and differences after learning using collaborative learning models. The research used a quantitative approach through an experimental method with a True Experiment Design in the form of a posttest-only control group design involving 58 Grade-III students of SD Mujahidin Pontianak as the population. The data were collected through observation and questionnaire. The data were once analyzed using the post-test data. In this research, the researchers discussed the impact of collaborative learning on students' interpersonal intelligence. The research findings indicated that the students' interpersonal intelligence was classified into moderate category. In this category, the students had the average ability to communicate and were adequately capable of forming their social relationships. Thus, it can be concluded that collaborative learning models impacts the students' interpersonal intelligence. The t-test result was 0.021 < 0.05, meaning that Hₐ was accepted, while Ho was rejected. Thus, the implementation of collaborative learning methods impacted the students’ interpersonal intelligence at grade III of SD Mujahidin Pontianak.